Arctic marine phytobenthos of northern Baffin Island. Issue 4 (7th July 2016) - Küpper, Frithjof C.; Peters, Akira F.; Shewring, Dawn M.; Sayer, Martin D. J.; Mystikou, Alexandra; Brown, Hugh; Azzopardi, Elaine; Dargent, Olivier; Strittmatter, Martina; Brennan, Debra; Asensi, Aldo O.; van West, Pieter; et al.
Abstract : Global climate change is expected to alter the polar bioregions faster than any other marine environment. This study assesses the biodiversity of seaweeds and associated eukaryotic pathogens of an established study site in northern Baffin Island (72° N), providing a baseline inventory for future work assessing impacts of the currently ongoing changes in the Arctic marine environment. A total of 33 Phaeophyceae, 24 Rhodophyceae, 2 Chlorophyceae, 12 Ulvophyceae, 1 Trebouxiophyceae, and 1 Dinophyceae are reported, based on collections of an expedition to the area in 2009, complemented by unpublished records of Robert T. Wilce and the first‐ever photographic documentation of the phytobenthos of the American Arctic. Molecular barcoding of isolates raised from incubated substratum samples revealed the presence of 20 species of brown seaweeds, including gametophytes of kelp and of a previously unsequenced Desmarestia closely related to D. viridis, two species of Pylaiella, the kelp endophyte Laminariocolax aecidioides and 11 previously unsequenced species of the Ectocarpales, highlighting the necessity to include molecular techniques for fully unraveling cryptic algal diversity. This study also includes the first records of Eurychasma dicksonii, a eukaryotic pathogen affecting seaweeds, from the American Arctic. Overall, this study provides both the most accurate inventory of seaweed diversity of the northern Baffin Island region to date and can be used as an important basis to understand diversity changes with climate change.